GVCs in Central Europe : a perspective of the automotive sector after COVID-19 - Černá, Iveta, 1979- (Vydavatel'stvo Ekonóm, 2022)
This scientific monograph is a joint output of more than a year of cooperation among the researchers from SGH Warsaw School of Economics, University of Economics in Bratislava (EUBA), Prague University of Economics and Business (VŠE), and the Centre for Economic and Regional Studies (CERS) in global value chains research in the automotive industry, emphasizing the value added importance in international business, particularly in the time of the COVID-19 pandemic impact. The authors hereby wish to express gratitude to the Visegrad Fund for financial support of the outputs within the project. They would also like to thank the reviewers for their valuable comments and experts from practice who participated in the questionnaires and structured interviews and colleagues and students who contributed to implementing the project outputs.